Eliciting blinks by transcutaneous electric nerve stimulation improves tear fluid in healthy video display terminal users: A self-controlled study. Issue 44 (4th November 2022) - Zeng, Weiting; Lou, Han; Huang, Quanbin; Li, Kunke; Liu, Xiuping; Wu, Kaili
Abstract : We aimed to elicit strong blinks among healthy video display terminal (VDT) users by periorbital transcutaneous electric nerve stimulation (TENS) and evaluate its impact on the tear fluid and visual task. Appropriate TENS conditions were evaluated to evoke strong blinks under minimum discomfort. Seventeen healthy VDT users with noninvasive Keratograph first breakup time (NIKf-BUT) 5-15 s and Ocular Surface Disease Index (OSDI) scores < 15 were recruited in this study. Before the trial, noninvasive Keratograph average breakup time (NIKa-BUT), tear meniscus height (TMH) and OSDI scores were evaluated. Before each TENS session, the volunteers played Tetris while the corresponding blink rate and Tetris scores were recorded. Then, the participants underwent 30 minutes of TENS, which evoked blinking of their right eye 20 times per minute. Tetris scores were evaluated again during TENS. The Tetris scores and corresponding blink rate were assessed after each TENS session while NIKa-BUT, TMH and OSDI scores were recorded after the third and sixth TENS sessions. We found that OSDI scores declined significantly after the sixth TENS ( P = .003). The NIKa-BUT of the right eye was promoted after the sixth TENS ( P = .02), and the TMH was higher after the third and sixth TENS in both eyes ( P = .03, P = .03 for right eyes respectively, P = .01, P = .01 for left eyes respectively). There was no significant difference between the adjusted Tetris scores before and during TENS ( P = .12). The blink rate before and after TENS were unaffected after 6 sessions ( P = .61). The results indicated that periorbital TENS effectively ameliorated ocular irritation and improved tear secretion and tear film stability by eliciting strong blinks in healthy VDT users without disturbing the visual task.